-6x+14=-34

Simple and best practice solution for -6x+14=-34 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6x+14=-34 equation:



-6x+14=-34
We move all terms to the left:
-6x+14-(-34)=0
We add all the numbers together, and all the variables
-6x+48=0
We move all terms containing x to the left, all other terms to the right
-6x=-48
x=-48/-6
x=+8

See similar equations:

| 2r+9/r=30 | | 0.75x=-18 | | 9m-1=16 | | X2+x-216=0 | | X=7,y=50 | | -13+104=7k+6k | | 16-2x=-2 | | X+(100-2x)+(x+(100-2x))=180 | | 9x2+x1=0 | | 14.5(11−x)=58 | | G(t)=4t^2-6t+7 | | 80=8.17x-30.98 | | -5-5x=47-7 | | 1.33=4/x | | 0=0.7x^2-28x-1075 | | 3y+1=119 | | 2(x+4)=-4(5x-1)+4x | | x^2=9/16 | | (x)=-2x(4x+5)(5x+5) | | 3y+2=119 | | x+12=x+15 | | 8/5(3x-1)=-3 | | -30+102=9m+9m | | X+(100-2x)+(x+3(100-2x)=180 | | b4+3=7 | | 6c=42.60 | | -20=2(x+8)-8x | | 0.25(12x-36=5x+18 | | k(-2)-5=-5 | | (3x+17)+(x+9)=14 | | 4(2x+6)=2(4x-5) | | 3x-2=24-4x+37 |

Equations solver categories